Identification of Fatty Acid Content of Sargassum sp. Seaweed and Ulva sp. in Different Seasonal Conditions - Alamsjah, Mochammad Amin; Md Nor, Adibi Rahiman bin (Journal of Aquaculture and Fish Health, 2024)
The active ingredients contained in seaweed prepare for pharmaceutical, cosmetic and food supplement needs from seaweed Sargassum sp. and Ulva sp. in different seasonal conditions it is thought to have a contribution of specific active ingredients. However, the fatty acid profile and morphology of the seaweed species Sargassum sp. obtained in the dry season and rainy season had the same results as the profile of the seaweed Ulva sp. which was collected in the Bangsring Beach area, Wongsorejo District, Banyuwangi, Indonesia. This is thought to be due to the extreme differences in dry season and rainy season conditions that have not yet resulted in real or drastic changes in the composition and quantity of macro and micronutrients, water quality and active fatty acid compounds as well as the adaptability of seaweed. Fatty acids of Sargassum sp. dominated by the composition of linoleic acid (C18:2), palmitic acid (C16:0) and oleic acid (C18:1), while the fatty acids of Ulva sp. dominated by the composition of heptadecanoic acid (C17:0), pentadecanoic acid (C15:0) and linoleic acid (C18:2n6).